Curative effect of hemoperfusion plus hemodialysis and hemodiafiltration in the treatment of elderly chronic renal insufficiency - Chen Hong-yu; Li Fang-ming; Zeng Li-mei (Linchuang shenzangbing zazhi)
Objective To explore the difference in curative effect between hemoperfusion（HP）plus hemodialysis（HD）and hemodiafiltration（HDF）in the treatment of elderly chronic renal insufficiency.Methods From January 2018 to January 2020,200 elderly in patients with chronic renal insufficiency were selected and divided into two groups in accordance with a random number table（n=100 each）.HDF group was subjected to HDF and HP+HD group HP plus HD.After 6-month treatment, two groups were compared with regards to oxidative stress level, inflammatory response level, renal function, sleep quality, quality-of-life and incidence of complications.Results No significant inter-group difference existed in oxidative stress level, inflammatory response level, renal function index, sleep quality score or quality-of-life score pre-treatment（P>0.05）.After 6-month treatment, they were significant improvements as compared to pre-treatment.There were statistically significant differences（P<0.05）.However, as compared with HDF group, oxidative stress level, inflammatory response level, renal function index, sleep quality score and quality-of-life score HP+HD group showed no statistically significant difference（P>0.05）;The complication rate was the same and the difference was not statistically significant（P>0.05）.Conclusion For elderly chronic renal insufficiency, HP+HD and HDF have the comparable curative effect.It may help to suppress oxidative stress and inflammation, improve renal function and patient prognosis and improve sleep quality.A proper selection is made in light of actual patient situations.